2014
DOI: 10.1007/s11252-014-0416-6
|View full text |Cite
|
Sign up to set email alerts
|

Rules of the roost: characteristics of nocturnal communal roosts of rainbow lorikeets (Trichoglossus haematodus, Psittacidae) in an urban environment

Abstract: Rainbow lorikeets (Trichoglossus haematodus) have successfully adapted to urban environments and are today abundant in many Australian cities. Here they often form noisy communal roosts and may damage infrastructure. While extensive studies on problem birds (mainly passeriforms) and their roosts have been conducted in other parts of the world, no detailed studies exist in Australia, where non-passeriform birds (e.g. parrots) can cause problems. This study investigates the roosting preferences of rainbow lorike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…This detailed study found that Rainbow Lorikeets preferred to roost in taller non-native roost trees with thick trunks and confirmed the tendency to use highly disturbed locations that were often close to lights. The roosts investigated in this study were, however, occupied by relatively small numbers of birds, with the largest roosts being classed as ' greater than 20' (Jaggard et al 2015).…”
Section: Guided By the Light: Roost Choice And Behaviour Of Urban Raimentioning
confidence: 77%
See 2 more Smart Citations
“…This detailed study found that Rainbow Lorikeets preferred to roost in taller non-native roost trees with thick trunks and confirmed the tendency to use highly disturbed locations that were often close to lights. The roosts investigated in this study were, however, occupied by relatively small numbers of birds, with the largest roosts being classed as ' greater than 20' (Jaggard et al 2015).…”
Section: Guided By the Light: Roost Choice And Behaviour Of Urban Raimentioning
confidence: 77%
“…Despite the spectacular growth in urban populations of Rainbow Lorikeets throughout Australia (Fitzsimons et al 2003;Lill 2009), little is known about most aspects of their roosting behaviour. An important exception is a recent study conducted in Sydney, Australia (Jaggard et al 2015). This detailed study found that Rainbow Lorikeets preferred to roost in taller non-native roost trees with thick trunks and confirmed the tendency to use highly disturbed locations that were often close to lights.…”
Section: Guided By the Light: Roost Choice And Behaviour Of Urban Raimentioning
confidence: 81%
See 1 more Smart Citation
“…, Jaggard et al. ) or have used radio‐telemetry to locate individual birds at roost sites (Jirinec et al. , Leavelle et al.…”
mentioning
confidence: 99%
“…Most birds undertake extended bouts of sleep at nocturnal roosts, but few investigators have studied the ecology of bird sleep. Of the few published studies, most have either focused on readily detected communally roosting species (Weatherhead 1983, Dominguez 2003, Smith et al 2008, Gilbert et al 2010, Jaggard et al 2014 or have used radio-telemetry to locate individual birds at roost sites (Jirinec et al 2015, Leavelle et al 2015. Although having some application for single-species studies, radio-tracking can be invasive, time consuming, and costly.…”
mentioning
confidence: 99%